Pengaruh Model Pembelajaran Guided Inquiry Terhadap Minat Belajar Peserta Didik Kelas X Dalam Pelajaran Sejarah Pada SMAN 16 Pekanbaru - Ria Rafianti (Jurnal Multidisiplin Indonesia, 2024)
This study began with the low learning outcomes of history lessons in Class X of SMAN 16 Pekanbaru. This is due to the low interest of students in learning and the learning model which is still conventional so that students are less active in the learning process in class. One of the efforts made to overcome this problem is to apply the Guided Inquiry learning model. This study aims to determine the effect of the Guided Inquiry learning model on students' interest in learning history lessons. This type of research is quasi-experimental. The population in this study were all students of Class X of SMAN 16 Pekanbaru. While the samples in this study were students of Class Xa and Class Xb. Students of Class Xa as an experimental class taught with the Guided Inquiry learning model. While students of Class Xb as a control class who learn with a conventional model. The instruments used were a questionnaire on learning interests and tests in the form of pretest-posttest questions. The collected data were analyzed using ANOVA calculations. The results of the study showed that there was no interaction of interest between motivation and the guided inquiry learning model in influencing students' learning interest, as evidenced by the results of the two-way ANOVA calculation obtained Fℎ???????????????????? 0.237 and a Sig. value of 0.626. Thus, it can be concluded that there is a significant influence by using the guided inquiry learning model and learning interest on the history learning outcomes of Class X students of SMAN 16 Pekanbaru.